2019
DOI: 10.1039/c8py01697f
|View full text |Cite
|
Sign up to set email alerts
|

A novel hydroxyl-containing polyimide as a colorimetric and ratiometric chemosensor for the reversible detection of fluoride ions

Abstract: A novel hydroxyl-containing polyimide film has been designed and fabricated as a chemosensor for the real-time visualization of F− with high selectivity and sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…86,87 In 2019, Wu et al reported a novel polyimide fluoride sensor and extractor based on hydrogen bonding interactions. 88 Their polymer (Figure 5) featured two hydroxyl groups capable of hydrogen bonding with fluoride ions in solution to produce quantitative changes in absorbance in a linear fashion with respect to concentration of fluoride ion. Fluoride ions were the only anionic species out of 11 that produced this response.…”
Section: Optical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…86,87 In 2019, Wu et al reported a novel polyimide fluoride sensor and extractor based on hydrogen bonding interactions. 88 Their polymer (Figure 5) featured two hydroxyl groups capable of hydrogen bonding with fluoride ions in solution to produce quantitative changes in absorbance in a linear fashion with respect to concentration of fluoride ion. Fluoride ions were the only anionic species out of 11 that produced this response.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…Left: Polyimide fluoride sensor developed by Wu and coworkers and its colorimetric response to fluoride ion. Reproduced with permission 88 . Copyright 2019, Wiley‐VCH.…”
Section: Hydrogen Bondingmentioning
confidence: 99%
“…They reported that the resulting polymer cannot only be used for the detection of F − but also the extraction of F − from the organic solution. Later, Wu et al (2019) designed a dye containing hydroxyl to detect F − in dimethyl sulfoxide (DMSO); this approach exhibited a detection limit of as low as 1.79 µM. Deng et al (2020) reported aminobenzodifuranone Graphical Abstract | The new dye, IDTI, firslty used as a fluoride anion chemosensor, has a high sensitivity with the fluoride anion detection limit of as low as 1 × 10 −7 M. And the IDTI solutions have the interesting color changing properties, once meet the fluoride anion, from red to yellow under ambient light and from purple to green under UV light were detectable by the naked eye.…”
Section: Introductionmentioning
confidence: 98%
“…Among polyimides, hydroxyl-containing polyimides (HPIs), as reactive polymers, can be further functionalized to prepare photosensitive polyimides, organic-inorganic polyimide composites, and thermo-crosslinkable polyimides, which are expected to be applied in optical lms, electronic packaging, liquid crystal displays, photoelectric functional devices, gas separation membranes and other elds. [11][12][13][14] In recent years, HPI, as the precursor of thermally rearranged (TR) polymers, has been widely concerned and investigated. 15 Aer thermal rearrangement reaction in solid state at 350-450 C, the benzoxazole structure from HPI was formed, accompanied by the emission of CO 2 .…”
Section: Introductionmentioning
confidence: 99%